Sistem e-INS: večno razhajanje med uporabniki in dejanskim stanjem - Vodopivec, Katarina (Podjetje in delo, 2013)
The author presents a short historic overview of developments of computerisation of insolvency registers. She continues with an introduction to the informatisation of e-INS system with electronic INS register, electronic files. Simultaneously, she demonstrates the differences between distinct groups of users of the e-INS system and their roles. The author also presents the activities for upgrading the existing system.
Keywords: elektronsko poslovanje; gospodarske družbe; informacijski sistemi; insolventnost; sodni postopek